Miles Franklin’s Growing Voice: Revisiting My Brilliant Career - Espák, Gabriella T. (Hungarian Journal of English and American Studies, 2022)
Rather than any of her more mature writing, Miles Franklin’s debut romance, My Brilliant Career, has been cemented into the canon of Australian literary nationalism. The novel received ambivalent immediate responses upon its publication in 1901 for its unflattering representation of the author’s kin and society. Subsequent criticism soon accepted Franklin’s oeuvre as part of the dominant male discourse of late nineteenth-century Australia, but after the 1970s her writing came under new scrutiny from a feminist aspect. Recently, she has been placed in a long tradition of female writing and discussed for gendered ventures. Nonetheless, however dedicated a feminist Franklin later became, she did not yet search for women’s greater self-realization in her debut but for her own identity and place in the world as an adolescent. This article argues that although Franklin’s classic has become an icon of both nationalist and feminist literature, the dichotomy of these readings can best be appeased through the adolescent ramps of its protagonist. It is an adolescent novel, in which a growing voice argues with her superiors, peers, and self, thereby exploring her authorial, gendered, and national identity. (GTE)